Establishing dental recall interval for Pakistani children: a longitudinal study - Muhammad Taqi; Jaffar Abbas Zaidi; Hafeez Shaikh; Adnan Sukkurwalla (Journal of the Pakistan Medical Association, 2021)
Objective: This study aims to determine the caries increment rate in children of 12 years of age after 6, 12 and18 months to establish appropriate dental recall interval. Subjects and Methods: Prospective longitudinal study of 18 months duration was conducted from May 2016 to October 2017 in the Bhakkar city of Punjab, Pakistan. School children of 12-years-old were selected in this study using convenience sampling. The caries progression rate was measured using Modified Beck’s method or adjusted caries increment. Descriptive analysis was conducted to estimate the response rate at baseline and at each follow-up, to estimate the number of children who attended the examinations, mean DMFT/DMFS scores and mean caries increments. Repeated measure ANOVA with post hoc test using Bonferroni correction was used to compare baseline mean caries increment with caries increment on 6, 12 and 18 months. Results: In the last follow-up, 183 children were present, giving a response rate of 81%. Significantly high caries increment among cavitated lesions was observed at 6 months (0.49±1.45, p=0.0001), 12 months (0.66±2.35, p=0.0001), and 18 months (0.86±2.39, p=0.0001) when compared with baseline caries increment. Continuous...